Association of MBL2 gene polymorphisms and MBL levels with dilated cardiomyopathy in a Chinese Han population - Yujie Mao; Hong Wei; Yugang Gong; Lei Peng; Yu Chen (BMC, 2024)
Abstract Background It has been reported that Mannose-binding lectin 2 (MBL2) gene polymorphisms and expression levels are related to dilated cardiomyopathy (DCM). This study aimed to investigate the potential association between MBL2 gene polymorphisms and the pathogenesis of DCM. Methods Five single nucleotide polymorphisms (SNPs) of the MBL2 gene were genotyped in 440 DCM patients and 532 controls in Southwest China. A luciferase reporter assay was used to detect the transcriptional activity the different genotypes. MBL serum levels, left ventricle ejection fraction (LVEF) and lower left ventricular end-diastolic diameter (LVEDD) were measured. Results The rs11003125 C allele increased the transcriptional activity of the MBL2 promoter compared with the rs11003125 G allele. The rs11003125 CC carriers had higher MBL serum levels, LVEF and LVEDD than the rs11003125 CG and GG carriers. Conclusions Our study first revealed that MBL2 polymorphisms and serum MBL levels were associated with DCM. Allele C in rs11003125 of MBL2 may upregulate the expression levels of MBL. High serum MBL levels may be a protective factor in DCM pathogenesis.